Menjadikan Alam Sebagai Ruang Belajar Dalam Pembelajaran Agama Hindu - I Ketut Muliarta (Jayapangus Press, 2018)
There is a misconception that the learning space is only a learning space effectively, if the classroom atmosphere is calm with the depiction of students sitting neatly. Such conditions still occur and create dull learning for the students. This also applies in Hinduism teaching that gives it in the classroom. One alternative to the condition is the Limit Changes that only use the study space. The solution of this is to make nature as a learning and learning space. In Hinduism there are several concepts such as Sang Hyang Widhi's Creation, Bhuana Agung, Bhuana Alit and Tri Hita Karana. Nature has various additions as a study space. By learning in nature, students are able to understand optimally the concepts without sacrificing the existing learning steps.